Knowledge, discipline and power in the Middle Ages: essays in honour of David Luscombe - Canning, Joseph (Studien und Texte zur Geistesgeschichte des Mittelalters, 2011)
David Luscombe : an appreciation / Christopher Brooke -- Pertransibunt plurimi : reading Daniel to transgress authority / Robert E. Lerner -- How can we know who holds legitimate power? : Dante on the right and the wrong uses of knowledge / Joseph Canning -- Knowledge of the origins : constructing identity and ordering monastic life in the Middle Ages / Gert Melville -- Seeking remedies for great danger : contemporary appraisals of Roger Bacon's expertise / Amanda Power -- The arrival of the pagan philosophers in the North : a twelfth-century florilegium in Edinburgh University library / Charles Burnett -- Questioning the music of the spheres in thirteenth-century Paris : Johannes de Grocheio and Jerome de Moravia OP / Constant J. Mews -- Papal policy on judging the orthodoxy of university masters : a research problem / William J. Courtenay -- Jean Gerson and the renewal of scholastic discourse 1400-1415 / Brian Patrick McGuire -- Controversy and compromise in religious communities in the eleventh and twelfth centuries / Giles Constable -- Pseudo-Dionysius Areopagita in der politischen Ekklesiologie der Augustinerschule des 14. Jahrhunderts / Jürgen Miethke -- The power of wisdom : four case studies of a late thirteenth century debate / Andreas Speer -- Liberty and limit : controlling and challenging knowledge in late medieval Europe / Martin Kintzinger -- Peter Abelard's theory of virtues and its context / John Marenbon -- The discipline of the republic and the knowledge of the citizens : what we may learn from late medieval endowment practice / Martial Staub -- A bibliography of the published writings of David Luscombe
"A bibliography of the published writings of David Luscombe"--P -- Includes bibliographical references and index
Keywords: Europe -- Intellectual life -- To 1500; Konferenzschrift -- 2006 -- Sheffield; Festschrift; Geschichte 500-1500; Macht; Bildung; Gelehrsamkeit; Europa